2000
DOI: 10.1021/jp993474x
|View full text |Cite
|
Sign up to set email alerts
|

Transition State for β-Elimination of Hydrogen from Alkoxy Groups on Metal Surfaces

Abstract: Experimental investigations of -hydrogen elimination from alkoxy and alkyl groups bound to a Cu(111) surface have been coupled with computational studies of gas-phase analogues to provide insight into the transition state for catalytic hydrogenation and dehydrogenation on metal surfaces. Previous studies have shown that fluorination increases the activation barrier (∆E act ) to -hydrogen elimination in ethoxy groups (RCH 2 O (ad) f RCHdO (ad) + H (ad) , where R ) CH 3 , CFH 2 , CHF 2 , CF 3 ) and propyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
5
32
1
Order By: Relevance
“…Although b-hydride elimination is the expected reaction pathway for CH 3 CH=O (CD 3 CD=O) formation from ethoxy groups (step 2), this does not exhibit a deuterium isotope effect in the acetaldehyde desorption temperature. This is in contrast with results revealing a deuterium kinetic isotope effect during b-hydride elimination in ethoxy groups on Cu surfaces [24].…”
Section: Mechanism Of Ch 3 Ch 2 Oh Decomposition On Zno 1 100 ð þcontrasting
confidence: 99%
“…Although b-hydride elimination is the expected reaction pathway for CH 3 CH=O (CD 3 CD=O) formation from ethoxy groups (step 2), this does not exhibit a deuterium isotope effect in the acetaldehyde desorption temperature. This is in contrast with results revealing a deuterium kinetic isotope effect during b-hydride elimination in ethoxy groups on Cu surfaces [24].…”
Section: Mechanism Of Ch 3 Ch 2 Oh Decomposition On Zno 1 100 ð þcontrasting
confidence: 99%
“…Gellman et al performed experimental studies of b-H elimination from alkyl and alkoxy species on Cu(111) and Pt(111). [6][7][8][42][43][44][45] By extracting structure-reactivity coefficients from the experimentally measured activation . They also concluded that the transition state was late for b-H elimination of ethyl on different Cu surfaces (endothermic reaction), but the structure sensitivity of the forward and reverse reactions was found to be similar.…”
Section: B-hydride Elimination Of Alkyl and Alkoxy Species On Cu And mentioning
confidence: 99%
“…4,5 Gellman et al have suggested related ideas for classifying the sensitivity of barriers for catalytic reactions occurring on solid surfaces to the structure of these surfaces. [6][7][8] This proposal involves two separate hypotheses. The structure sensitivity postulate (SSP) asserts that the activation barriers for catalytic reactions occurring on solid surfaces are more sensitive to the structure of the surface if the transition state is late rather than early.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades the chemistry [1][2][3][4][5] and the reaction kinetics [6][7][8] of alkyl moieties below C 3 prepared by the dissociative adsorption of alkyl halides on transition-metal have been widely studied. These results show that the alkyl moieties of C 2 or C 3 decompose on transition-metal surface by b-hydrogen elimination to form olefins (ethylene or propylene) and no C-C coupling reactions have been observed [1][2][3][4][5][6][7][8]. Fluorine-substituted alkyl surface moieties have also drawn increasing attention because the replacement of hydrogen with fluorine can result in a marked change in the physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%